Morphology and kinematics of the gas envelope of the Mira binary W Aquilae*This paper makes use of the following ALMA data: ADS/JAO.ALMA#<2012.1.00524.S>. ALMA is a partnership of ESO (representing its member states), NSF (USA) and NINS (Japan), together with NRC (Canada) and NSC and ASIAA (Taiwan), and KASI (Republic of Korea), in cooperation with the Republic of Chile. The Joint ALMA Observatory is operated by ESO, AUI/NRAO and NAOJ. The data are retrieved from the JVO portal (http://jvo.nao.ac.jp/portal) operated by the NAOJ. (July 2016) - Hoai, Do Thi; Nhung, Pham Tuyet; Diep, Pham Ngoc; Phuong, Nguyen Thi; Tuan-Anh, Pham; Thao, Nguyen Thi; Darriulat, Pierre
Abstract: We analyse ALMA observations of the 12 CO(3-2) emission of the circumstellar envelope (CSE) of the Mira variable binary star W Aql. These provide, for the first time, spatially resolved Doppler velocity spectra of the CSE up to angular distances to the central star of ∼ 5″ (meaning some 2000 AU). The exploratory nature of the observations (only five minutes in each of two different configurations) does not allow for a detailed modelling of the properties of the CSE but provides important qualitative information on its morphology and kinematics. Emission is found to be enhanced along an axis moving from east/west to north-east/south-west when the angular distance from the central star projected on the plane of the sky increases from zero to four arcseconds. In parallel, the Doppler velocity distribution displays asymmetry along an axis moving from east/west to north-west/south-east. The results are discussed in the context of earlier observations, in particular of the dust morphology.